Basic design and cost optimization of a hybrid power system in rural communities in Afghanistan - Sadiqi, Mahdi (Kansas State University, 2012)
In Afghanistan, electricity is mostly generated by hydroelectric, diesel and natural gas generators. A significant amount of electricity also is imported from neighboring countries. Accessibility of electricity is mostly limited to the capital and main towns. The government of Afghanistan and other development organizations, such as The United States Agency for International Development (USAID) and Deutsche Gesellschaft für Internationale Zusammenarbeit (German Agency for International Cooperation “GIZ”), are striving to develop accessibility of electricity to remote communities by supporting the local population of people to enhance living conditions. Although some of these remote communities are served by local diesel fuel generators for just a couple of hours during the night, still most communities do not have access to electricity and they are using wood and kerosene as major sources of energy in cooking, heating and lighting. For those remote communities who are served by local diesel fuel generators, the cost of electricity is much higher than from the national grid. On the other hand, grid extensions are too expensive and, in some cases, impossible for such communities because of the geographical features of Afghanistan. Afghanistan is a mountainous country which receives a significant amount of snow during the winter and once it melts the water runs into rivers, lakes and streams. Therefore mostly it does not face any shortage of running water during the year. Also Afghanistan has plentiful wind and solar energy. Therefore, small hydro-power, wind turbine and solar energy are attractive renewable energy sources for remote communities. The development of such a hybrid power system is a complex process and technical expertise is essential in design and construction phases. The main challenges are the high cost of civil works and equipment, technical expertise for design and construction and encouragement of local people for the support of the project. This report will give an insight into design, cost-effectiveness and feasibility of the system using HOMER in order to encourage private investors and local community people to take advantage of this potential available in Afghanistan and be convinced of the sustainability for investments in micro-hydropower, wind and solar.
Keywords: Hybrid Power System; Micro-hydro; Renewable; Rural Electrification; Cost Effectiveness; Afghanistan; Electrical Engineering (0544)